2014
DOI: 10.1007/s11999-013-3351-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Analgesia Versus Epidural Plus Femoral Nerve Block After TKA: A Randomized, Double-blind Trial

Abstract: Background Pain management after TKA remains challenging and the efficacy of continuously infused intraarticular anesthetics remains a controversial topic.Questions/purposes We compared the side effect profile, analgesic efficacy, and functional recovery between patients receiving a continuous intraarticular infusion of ropivacaine and patients receiving an epidural plus femoral nerve block (FNB) after TKA. Methods Ninety-four patients undergoing unilateral TKA were prospectively randomized to receive a spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
3
25
1
5
Order By: Relevance
“…Furthermore, the reduced consumption of narcotics in Group B patients may be the major factor leading to the reduced incidence of nausea, vomiting and dizziness that we observed in Group B. In a previous study [18], we found ropivicaine infusion alone was associated with higher VAS pain scores during the first 48 h compared to Epidural/FNB. In this study, addition of the SNB has eliminated this difference.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, the reduced consumption of narcotics in Group B patients may be the major factor leading to the reduced incidence of nausea, vomiting and dizziness that we observed in Group B. In a previous study [18], we found ropivicaine infusion alone was associated with higher VAS pain scores during the first 48 h compared to Epidural/FNB. In this study, addition of the SNB has eliminated this difference.…”
Section: Discussionsupporting
confidence: 51%
“…Femoral nerve blocks are now well known to be associated with prolonged quad weakness which slows the progression of post-op mobilization and increases the risk of falling during the hospital stay [6,8,10,18,20,22]. Our current approach combines intra-articular infusion of ropivicaine with a saphenous nerve block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Außerdem besteht aufgrund motorischer Blockade und Sensibilitätsverlust im Bereich der unteren Extremität eine erhöhte Sturzgefahr. Folglich kommt es zu einer verzögerten postoperativen Mobilisation [12,21]. Zusätzlich ist die Applikation des Katheters technisch nicht immer möglich und bedarf nicht selten eines deutlichen zeitlichen Aufwandes im Rahmen der Operationsvorbereitung.…”
Section: Hintergrund Und Fragestellungunclassified
“…From these we identified 12 eligible RCTs. [3][4][5][6][7][8][9][10][11][12][13][14] Inter-observer agreement for trial eligibility was good (kappa = 0.75; SE 0.053). Table I reports the characteristics of the included trials and the local anaesthetic protocols used in the trials.…”
Section: Trial Identification and Selectionmentioning
confidence: 95%